1989
DOI: 10.1620/tjem.159.75
|View full text |Cite
|
Sign up to set email alerts
|

Some features of the metastatic cancer cells in prostaglandin production.

Abstract: In order to establish metastatic lesions, 2.5>< 106 AH100B cells were injected into the left carotid artery of male Donryu rats. Each metastatic nodule in the liver or kidney, 1 mm or less in diameter, thus obtained was then injected into the peritoneal cavity in which these metastatic cells come to free. About 3 weeks later, each ascites was collected from the rats, while not bloody. Then, cancer cells obtained from each ascites were suspended in Dulbecco's PBS without Ca2+ and Mg2+ (pH 7.2) after washing. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…These results suggest that PGs produced by hepatic metastatic cancer cells might play an important role in hepatic metastatic formation. cancer metastases; liver; gastric cancerWe have been investigating features of prostaglandin (PG) synthesis of the metastatic cancer cells, using an animal model in which AH100B (a rat hepatoma cell line) cells were injected into the carotid artery of male Donryu rats (Nakazawa et al 1985(Nakazawa et al , 1989(Nakazawa et al , 1991. In this paper, we will deal with some features of PG synthesis in cancer cells metastasized into the liver from the gastric cancer lesion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that PGs produced by hepatic metastatic cancer cells might play an important role in hepatic metastatic formation. cancer metastases; liver; gastric cancerWe have been investigating features of prostaglandin (PG) synthesis of the metastatic cancer cells, using an animal model in which AH100B (a rat hepatoma cell line) cells were injected into the carotid artery of male Donryu rats (Nakazawa et al 1985(Nakazawa et al , 1989(Nakazawa et al , 1991. In this paper, we will deal with some features of PG synthesis in cancer cells metastasized into the liver from the gastric cancer lesion.…”
mentioning
confidence: 99%
“…Then, each cell suspension containing 1>< 106 cancer cells was mixed with 50 ,ul of the PBS containing 0.2,uCi of [1-14C] arachidonic acid (AA) (New England Nuclear, Boston, MA, USA) and incubated at 25°C for 30 min. After the incubation, PGs formed were extracted and separated by means of thin-layer chromatography (TLC) as described previously (Nakazawa et al 1989). As authentic samples, AA (Merk, Germany), 6-ketoprostaglandin F1a (6-keto-PGF1a), prostaglandin F2a (PGF2a), prostaglandin E2 (PGE2), prostaglandin D2 (PGD2) and thromboxane B2 (TXB2) (Ono Pharmaceutical Co. Ltd., Osaka), 5,ug each per plate, were used.…”
mentioning
confidence: 99%
“…These results suggest that PGs produced by hepatic metastatic cancer cells might play an important role in cancer metastasis. cancer metastasis; prostaglandin; liver; intestinal cancer Authors (Nakazawa et al 1985(Nakazawa et al , 1989(Nakazawa et al , 1991 have reported features of PG synthesis of the metastatic cancer cells, using an animal model in which AH100B (a rat hepatoma cell line) cells were injected into the carotid artery of male Donryu rats.In this article, we will deal with some features of PGs synthesized by cancer cells which metastasized into fiver from the small intestinal cancer lesion.Materials and methods. As experimental animals, male Donryu rats (Nikon Rat Co. Ltd., Urawa) weighing 100 to 120 g were used and fed with a pellet diet, NF (Oriental Yeast Co. Ltd., Tokyo).Tumor.…”
mentioning
confidence: 99%
“…These results suggest that PGs produced by hepatic metastatic cancer cells might play an important role in cancer metastasis. cancer metastasis; prostaglandin; liver; intestinal cancer Authors (Nakazawa et al 1985(Nakazawa et al , 1989(Nakazawa et al , 1991 have reported features of PG synthesis of the metastatic cancer cells, using an animal model in which AH100B (a rat hepatoma cell line) cells were injected into the carotid artery of male Donryu rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation